2013
DOI: 10.1371/journal.pone.0064985
|View full text |Cite
|
Sign up to set email alerts
|

Y-Chromosome Analysis in Retuertas Horses

Abstract: Several studies based on a variety of genetic markers have attempted to establish the origins of horse domestication. Thus far a discrepancy between the results of mitochondrial DNA analysis, which show high levels of diversity, and results from the Y-chromosome, with almost no genetic variability, has been identified. Most previous work on the horse Y-chromosome has focused on widespread, popular breeds or local Asian breeds. It is possible that these breeds represent a reduced set of the genetic variation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…In horses, however, the assembly for the whole NRY region is not available yet, as the reference genome was characterized from a single mare individual (Wade et al 2009). Studies targeting specific NRY regions have shown limited variation, with haplotypes differing by one mutational step at best, which indicates that only a handful of paternal lines survived until present-day in domestic horses (Lindgren et al 2004;Brandariz-Fontes et al 2013;Wallner et al 2013;Kreutzmann et al 2014;Han et al 2015). By contrast, analyses initially based on the mtDNA control region (D-loop) (Lister et al 1998;Vilà et al 2001;Jansen et al 2002;Cieslak et al 2010), and more recently on complete mitochondrial genomes (Lippold et al 2011a;Achilli et al 2012), revealed horses as the domestic animal showing one of the largest pools of mitochondrial genetic diversity.…”
Section: Gender-biased Contributions To Domesticationmentioning
confidence: 99%
“…In horses, however, the assembly for the whole NRY region is not available yet, as the reference genome was characterized from a single mare individual (Wade et al 2009). Studies targeting specific NRY regions have shown limited variation, with haplotypes differing by one mutational step at best, which indicates that only a handful of paternal lines survived until present-day in domestic horses (Lindgren et al 2004;Brandariz-Fontes et al 2013;Wallner et al 2013;Kreutzmann et al 2014;Han et al 2015). By contrast, analyses initially based on the mtDNA control region (D-loop) (Lister et al 1998;Vilà et al 2001;Jansen et al 2002;Cieslak et al 2010), and more recently on complete mitochondrial genomes (Lippold et al 2011a;Achilli et al 2012), revealed horses as the domestic animal showing one of the largest pools of mitochondrial genetic diversity.…”
Section: Gender-biased Contributions To Domesticationmentioning
confidence: 99%
“…In contrast to the plenty of mutations in the mitochondrial genome and on the Y chromosome http: //www.openveterinaryjournal.com A.D. Khaudov et al Open Veterinary Journal, (2018), Vol. 8(1): 40-46 ________________________________________________________________________________________________________ variation of pre-domestic horses (Lippold et al, 2011), no diversity was detected in the Y chromosome of domestic horses awhile (Brandariz-Fontes et al, 2013;Lindgren et al, 2004). In the last years, a few polymorphic sites were found in modern horses leading to a small number of haplotypes in contemporary domestic stallions (Ling et al, 2010;Wallner et al, 2013Wallner et al, , 2017Kreutzmann et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Y chromosome, because of its male specific feature in the mammalian genome, unpairing with X chromosome during the meiosis, provides a powerful tool to trace the paternal origin of mammals ( Skaletsky et al, 2003 ). Despite most of the studies on Y chromosome in domestic horse revealed no genetic variation ( Lindgren et al, 2004 ; Wallner et al, 2004 ; Lau et al, 2009 ; Brandariz-Fontes et al, 2013 ), a recent study on equine Y chromosome short tandem repeats (Y-STR) detected two Y chromosome haplotypes in Chinese domestic horses ( Ling et al, 2010 ), though, no Y-STR polymorphism was found in horses from Portugal, Spain and France ( Brandariz-Fontes et al, 2013 ), indicating horse Y chromosome is not homogeneous and Chinese horse might display more abundant Y chromosome diversity. In addition, Chinese indigenous horse revealed a higher diversity level in comparison with Spanish horses, German draught horses, Swiss horses, Norwegian horses, Portuguese Sorraia and Friesian horse and Japanese native horse breeds using 27 microsatellite markers ( Ling et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%